ANALISIS PENERAPAN PSAK NO 45 TENTANG PELAPORAN KEUANGAN ORGANISASI NIRLABA - Yeyen Suendra; Suharyono Suharyono; Ledy Setiawati (AKUNTABEL, 2015)
Organization of the mosque is one of the non-profit organization in the field of religion, in accordance with Statement of Financial Accounting Standards (PSAK 45) of 2011 on a non-profit organization, that non-profit organizations and also should have the right to make financial statements and  report  to  the  users  of  financial  statements.  For  that  mosques  should  also  entitled  to  make statements and financial accountability and reporting to users of financial statements of the pilgrims who are the main source of income of the mosque, even donors from outside even so, the pilgrims and more active donors to provide funding for the mosque propaganda activities. The purpose of the study was to analyze in the preparation of financial statements Masjid Islamic Centre Samarinda in East Kalimantan with reference to Pernyataan Standar Akuntansi Keuangan (PSAK) NO. 45 of 2011 on a non-profit       organization. The analytical tool used in this study, Pernyataan Standar Akuntansi Keuangan (PSAK)  NO. 45 of 2011 on a non-profit organization. This is done to determine whether whether Masjid Islamic Centre Samarinda in East Kalimantan has made recording of financial statements in accordance with PSAK NO. 45 to the delivery of relevant information to meet the interests of the users of the financial statements of both internal and external parties. Based on the research that has been conducted on the financial statements Masjid Islamic Centre Samarinda in East Kalimantan was found that there are still some that are not in accordance with PSAK NO. 45 That is not reported Statements of Financial Position, Statement of Activities, not classifying revenues and expenses properly. Keyword: PSAK NO 45 Tahun 2011